Antioxidant, anthelmintic and antibacterial activities of red juniper (Juniperus phoenicea L.) essential oil. Issue 2 (4th March 2022) - Meriem, Aouadi; Msaada, Kamel; Sebai, Essia; Aidi Wannes, Wissem; Salah Abbassi, Mohamed; Akkari, Hafidh
ABSTRACT: This study investigated the antioxidant, anthelmintic and antibacterial activities of essential oil obtained from red juniper ( Juniperus phoenicea ) leaves. Red juniper essential oil yield was 0.80%. The GC-MS analysis of this essential oil showed that α -pinene (74.14%) was the predominant component. The anthelmintic activity assay of red juniper essential oil was performed on Haemonchus contortus using egg hatch assay (EHA) and adult worm's motility assay (AWMA). In the AWMA, essential oil induced inhibition of 76.18% at 1 mg/mL. The antibacterial activity of red juniper essential oil was effective against six human pathogenic bacteria including Listeria monocytogenes, Staphylococcus aureus, Bacillus cereus, Salmonella enteritidis, Salmonella typhimurium and Escherichia coli ). These results suggested that red juniper essential oil could also be employed for developing new anthelmintic, antimicrobial and antioxidant agents.